2022
DOI: 10.3390/ijerph20010374
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Networking Capability and Hospital Performance in Indonesia’s Medical Tourism Sector

Abstract: Medical tourism is an industry that is currently developing, but research that focuses on the analysis of supply and institutions as a unit in Indonesia is sparse. This research aims to investigate the variables of digital transformation and resource integration that influence hospital performance, considering the expansion of hospitals’ capacities for networking in medical tourism. A structural equation model is used to evaluate the hypothesis. According to our findings, digital transformation and resource in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 76 publications
2
4
0
Order By: Relevance
“…Similarly, the findings showed a positive relationship between NC and FP which is consistent with previous studies (Akmalia & Astuti, 2022;Cenamor et al, 2019;Ediansyah et al, 2022;Wegner et al, 2023). This finding shows that the leveraged network capability of Saudi firms can facilitate access to diverse resources, discovery of new opportunities, and adaptation to changing market demands, thus improving firms' financial and market performance.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Similarly, the findings showed a positive relationship between NC and FP which is consistent with previous studies (Akmalia & Astuti, 2022;Cenamor et al, 2019;Ediansyah et al, 2022;Wegner et al, 2023). This finding shows that the leveraged network capability of Saudi firms can facilitate access to diverse resources, discovery of new opportunities, and adaptation to changing market demands, thus improving firms' financial and market performance.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, NC played a full mediating role between DPC and FP consistent with the studies of Cenamor et al (2019), Bhatti et al (2022) and Akmalia & Astuti (2022). It is noteworthy that our findings also align with the findings of Ediansyah et al (2022) which also showed NC as a full mediator on digital transformation and FP relationship.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations